Knowledge, attitude, and practice of medication use among pregnant women in Riyadh City: a cross-sectional study - Almuhareb, Alanoud; Al Sharif, Abdullah; Cahusac, Peter (Frontiers in Global Women's Health, 2024)
Introduction Medication use during pregnancy is limited by the scarcity of safety data for many drugs. The use of certain drugs during pregnancy can be teratogenic. Overestimating teratogenic medication risk could have serious consequences from drug non-adherence. Assessing and understanding the knowledge, attitude, and practice of medication use among pregnant women is crucial to optimizing the health of pregnant women and their fetuses. Methodology An observational cross-sectional study used convenience and snowball sampling with a self-administered online questionnaire in 562 pregnant women from Riyadh City. The questionnaire used was adapted from previously published surveys. The survey included sections on sociodemographic background, awareness of medication risks, medication use during pregnancy, sources of drug information, and statements from the Beliefs about Medicines Questionnaire (BMQ), both general and pregnancy-specific. Results Medication use during pregnancy was reported by 44.7%. The primary source for medication information for the majority was the physician. Over 58% indicated inadequate or inconsistent information about medication from physicians. Additionally, 65.7% confirmed not receiving sufficient or inconsistent information from pharmacists during medication dispensing. The responses to the questionnaire reveal a commendable level of knowledge and positive attitude and practice. However, variations could be found in these responses. Overall, no evident relationships were observed between predictors and responses, except in specific statements that indicated a positive association between beliefs and higher levels of education and youth. Conclusion The results suggest a positive knowledge, attitude, and practice level. However, there was hesitancy and a restrictive attitude towards medication during pregnancy. The study identified inadequate education provided by healthcare professionals, thus presenting an area for improvement to enhance the safety and efficacy of medication use during pregnancy.